Machine design design of transmission systems - Jalaludeen, S. Md (Anuradha Publications, 2012)
In this book, the design of common power transmission elements such as belt drives, chain drives, rope drives, gear drives, cam drives ect., have been discussed in detail in an exceptionally simple manner with the aid of fundamental theories, simple procedure and numerous problems related to various fields of engineering and science. A part from the above drives the design details related to power screws, pawl & ratchet and geneva machanism stc., have been clearly explained.